Inhibition of SARS–CoV–2 NSP–15 by Uridine–5′–Monophosphate Analogues Using QSAR Modelling, Molecular Dynamics Simulations, and Free Energy Landscape - Mohammed Merae Alshahrani (Saudi Pharmaceutical Journal)
SARS–CoV–2 is accountable for severe social and economic disruption around the world causing COVID–19. Non–structural protein–15 (NSP15) possesses a domain that is vital to the viral life cycle and is known as uridylate–specific endoribonuclease (EndoU). This domain binds to the uridine 5′–monophosphate (U5P) so that the protein may carry out its native activity. It is considered a vital drug target to inhibit the growth of the virus. Thus, in this current study, ML–based QSAR and virtual screening of U5P analogues targeting Nsp15 were performed to identify potential molecules against SARS–CoV–2. Screening of 816 unique U5P analogues using ML–based QSAR identified 397 compounds ranked on their predicted bioactivity (pIC50). Further, molecular docking and hydrogen bond interaction analysis resulted in the selection of the top three compounds (53309102, 57398422, and 76314921). Molecular dynamics simulation of the most promising compounds showed that two molecules 53309102 and 57398422 acted as potential binders of Nsp15. The compound was able to inhibit nsp15 activity as it was successfully bound to the active site of the nsp15 protein. This was achieved by the formation of relevant contacts with enzymatically critical amino acid residues (His235, His250, and Lys290). Principal component analysis and free energy landscape studies showed stable complex formation while MM/GBSA calculation showed lower binding energies for 53309102 (ΔGTOTAL = –29.4 kcal/mol) and 57398422 (ΔGTOTAL = –39.4 kcal/mol) compared to the control U5P (ΔGTOTAL = –18.8 kcal/mol). This study aimed to identify analogues of U5P inhibiting the NSP15 function that potentially could be used for treating COVID–19.